Avaliação das proteínas envolvidas nas etapas iniciais da via de sinalização da insulina em músculo masseter de animais tratados com dexametasona - França, Igor Rabelo de (2017)
Insulin resistance is partly caused by molecular changes in the level and/or degree of phosphorylation of proteins located downstream of the insulin receptor/insulin-like growth factor receptor (IR/IGF1R) signaling pathway that occurs in the skeletal muscle, liver, and adipose tissue. However, few studies have investigated the intracellular insulin pathway in the masseter muscle under altered metabolic conditions such as obesity and diabetes. Therefore, this study aimed to analyze the IR/IGF1R signaling pathway in the masseter muscle of rats treated with dexamethasone (a glucocorticoid that induces manifestations of insulin resistance at high concentrations). Male Wistar rats were divided into two groups: control group, intraperitoneally injected with 0.9% NaCl (saline solution), and dexamethasone group, intraperitoneally injected with a dexamethasone solution (1 mg/kg body weight) for 10 consecutive days. Sections of the masseter muscle were removed at time zero and after the infusion of regular insulin into the portal vein. The administration of dexamethasone induced body weight loss without changing the masseter muscle weight. In addition, it reduced the expression of total IR and PI3K proteins, with the total levels of IRS1, AKT, and ERK1 remaining unchanged compared with the levels in the control group. The degree of phosphorylation/activity of IRS1 after insulin stimulus increased in the control group but not in the dexamethasone group. The degree of phosphorylation of AKT increased in both groups, but this increase was attenuated in the dexamethasone group. We suggest that the degree of phosphorylation/activity in the masseter muscle is different from that in other muscle territories.